Electromagnetic field decay in high-frequency flare discharge plasma - Lutsenko Yu. Yu. (2006, 2006)
Axial profiles of the amplitudes of harmonic components in the electric field of a flare discharge in air and argon have been measured. The frequency dependence of the coefficient of electromagnetic field decayin the discharge plasma exhibits a nonmonotonic character.